Uma leitura vertiginosa: os fanzines punks no Brasil e o discurso da união e conscientização : (1981-1995) - Milani, Marco Antonio [UNESP] (2015)
The development of punk in Brazil happened by the end of the military dictatorship. It made essential, to this group of young people, the events concerning the redemocratization of the Constituent Assembly and the direct elections. However, this new democracy gave room to many different political organizations that became part of the Brazilian daily life. Such events were essential to fanzines, that made efforts to discuss them and, sometimes, looked into them for inspiration to their material and discursive form. Thus, punk fanzines manifest the concept of bricolage, inherent of the punk esthetics, as the axis of its discursive and reading practices. Through the collage of excerpts of other prints, fanzines subverted the original meanings of the cutouts they used, inserting them in reading supports of confuse appearance, making the reader divagate along the pages. Not coincidentally, they were part of a discursive form that sounded confuse and truncated, hard to understand for the public outside the punk subculture. This discourse made efforts in restricting the internal violence of the group and represent it as an agent committed to transforming the country and the world. Such discourse was named union and awareness.